Molecular simulations of adsorption and separation of ethylene/ethane and propylene/propane mixtures on Ni2(dobdc) and Ni2(m-dobdc) metal-organic frameworks. Issue 5 (24th March 2018) - Gholami, Mohammad; Yeganegi, Saeid
Abstract: Porous solid adsorbents have received considerable attention as a promising alternative to the traditional cryogenic distillation for separating olefin/paraffin mixtures. In this work, we studied pure components as well as ethylene/ethane and propylene/propane binary mixtures uptakes and selectivities at 318 K and 1 bar into metal-organic frameworks Ni2 (dobdc) and Ni2 (m-dobdc) using GCMC simulations. We used DFT method to modify the potential model of carbon–carbon double bond in unsaturated hydrocarbons. GCMC results show that ethylene and ethane uptakes on Ni2 (m-dobdc) are higher than that of Ni2 (dobdc) but propylene and propane uptakes are equal in Ni2 (m-dobdc) and Ni2 (dobdc). Also, Ni2 (m-dobdc) has higher selectivity than Ni2 (dobdc) for separation of ethylene/ethane and propylene/propane mixtures.